A STUDY OF CORPORATE GOVERNANCE IN STATE OWNED ENTERPRISES IN THE KENYAN ENERGY SECTOR: KENGEN VS. GDC - Gondi, Wendy Flavian Achieng (2013)
Over the years, Kenya’s public sector has been plagued by numerous corruption cases which have crippled institutions, inefficiencies which have caused the government massive losses, gross misconduct by boards and management when it comes to equitable and fair distribution of employment opportunities which has denied institutions with relevant and skilled labor they deserve. There is also the aspect of political interference, a major stumbling block in efficient management of public institutions. In an ever-changing global economy, emerging markets are adopting corporate governing practices that are put in place to curb certain undue influences that stand the risk of affecting economic growth. These practices, for a long time, have been the backbone of private sector management but have slowly and surely made their way in to management practices of the public sector. Kenya has taken up these management practices with the key bias of improving the running and management of its state-owned enterprises. The government has partnered with Center for Corporate Governance, a private sector initiative that which has a distinct and key mandate that entail training, education, research, monitoring, evaluation and advocacy. It was realized that there was great opportunity of initiating this practices through training of directors of corporations both in the public and private sector. There was opportunity to conduct research that will enable organizations address day-to-day issues, problems and limitations that can foster or hinder the growth of good corporate governance ideologies. There was an opportunity in the development of mechanisms that will help guide organizations towards active implementation and subsequent use of these practices of corporate governance. Compliance to these practices was also not going to be unnoticed, as high standards of compliance would be rewarded. The Kenyan government took up this responsibility and the development of training manuals that would enable faster and efficient system integration and based on this, a research program was designed in order to make this trainings sustainable. In addition, Kenya is also a member state of The Organization for Economic Co-operation and Development which is a body that helps member government fight poverty through initiative that foster financial stability. This enables a state or government take ownership responsibility, which is beneficial for accountability purposes. All these initiatives that the Kenyan government are putting in place comes from the realization that as a government, it needs to play an active role in the management of public sector institution and especially state owned enterprises and that these enterprise contribute a great deal to the country’s GDP and thus have to be run efficiently so as to achieve maximum profitability, generate maximum revenue and at the same time be cost effective. This research will delve into the world of corporate governance perception in Kenya’s energy sector. We’ll get to see its successes, failures and learning’s. The research will strive to show how best, two key companies in the energy sector are coping with corporate governance management practices especially with regards to their day-to-day running of company business.